Towards Islamic English - Elsied, Ahmed Gasm (Tafakkur; Vol 4 No 1 (2002), 2002)
Islamic English is the English Language modified to enable it to carry Islamic proper nouns and meanings without distortion, and thus to serve the linguistic needs of Muslim users of the English Language . As new notion , Islamic English '' raises three questions : who are the Muslim users of the English Language? What is the nature of the distortion claimed to exist ? What is the needed rectification?